Applying for Research Electives - Keogh, Conor (Trinity Student Medical Journal, 2016)
Undertaking a summer research elective is a great way to assess whether academic research is something you would be interested in incorporating into your future training or career. It can also add something different to your CV when applying for more academically oriented specialisation training programmes. Despite this, very few people take advantage of the opportunities available to them and many that are interested in summer research simply don’t know where to start looking. This article will give a brief overview of where to start when considering a research elective, followed by first-hand accounts from students who have previously completed research electives.